15N NMR spectroscopy unambiguously establishes the coordination mode of the diimine linker 2-(2′-pyridyl)pyrimidine-4-carboxylic acid (cppH) in Ru(ii) complexes1. Issue 35 (21st September 2015) - Battistin, Federica; Balducci, Gabriele; Demitri, Nicola; Iengo, Elisabetta; Milani, Barbara; Alessio, Enzo
<x xml:space="preserve">Abstract</x> The 15N NMR chemical shifts, obtained through 1H, 15N-HMBC spectra at 15N natural abundance, unambiguously establish the coordination mode of cppH (viaNo or Np) in a series of Ru(ii) compounds.